Frequency of food intakes and dental caries in a Malaysian dental student group - Sulinda, D.; Marina, M.M.; Rahim, Z.H.A.; Ferguson, D.B. (2011)
Objective: Although the relationship between snack food eating and dental caries has been investigated in the United States and European groups, no data exist for Asian snack foods and diets. Our objective was to investigate snack food eating and dental caries in a Malaysian dental student group. Methodology: Frequency of eating was assessed on a basis of 2 weekday and 2 weekend day diaries for non-fasting students and one weekday and one weekend day during Ramadan, and a similar set outside Ramadan for fasting students. The sucrose and carbohydrate composition of between meal snacks and drinks was identified. The total number of decayed, missing, and filled teeth was recorded by two dental examiners. Results: The modal number of total food intakes was 2 or 3 per day on both weekdays and weekends. The number of between-meal snacks and drinks varied between 0 and 5. They were either high sucrose/low carbohydrate or high sucrose/high carbohydrate. DMFS scores were very low in all subjects but increased with between- meal snack intakes, particularly in the high sucrose/low carbohydrate category. Conclusions: Malaysian students had relatively low frequencies of food intakes but there was still an association between frequency of between-meal snacks and caries rates, as in Western countries.